THE NOOSPHERE STAGE AND THE INCREASING RESPONSIBILITY OF MANKIND IN THE PERSPECTIVE OF THE PLANET EARTH - Panjiev Suhrob (American Journals Publishing, 2022)
This article presents the ideas of the gradual development of the relationship between society and nature. The meaning of the concept of the noosphere is based on its importance in harmonizing all the spiritual aspects of the human mind and personality in general.
Keywords: Noosphere, society and nature, spiritual aspects, Vernadsky's biosphere theories.